Existential-Phenomenological Psychologist’s Action (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
Heidegger's Dasein analytic presents existence as an indeterminate being having to deal with the fact that it is and has to be. The psychologist who grounds his work in Heidegger's existential phenomenology must therefore assume himself as an existence encountering other existences.
Keywords: Martin Heidegger; existential-phenomenological psychology; Daseinsanalysis